(untitled) (Annals of Medical Research, 2021)
Aim: To compare IVF-ICSI outcomes in single-versus-double lumen oocyte retrieval needles in patients diagnosed with unexplained infertilityMaterials and Methods: A total of 188 patients aged 23-33 years who were diagnosed as unexplained infertility and underwent IVF/ICSI treatment were included and divided into two groups according to whether the catheter used in oocyte collection was single or double lumened: group 1 patients with single lumen (n: 59) and group 2 patients with double lumen (n:129). In addition, patients were divided into two subgroups according to the treatment protocol: antagonist protocol (n:134; 45 patient in group 1 and 89 patient in group 2) and long agonist protocol (n:54; 14 patient in group 1 and 40 patient in group 2). Results: Implantation rate (32.2% vs. 48.1%, p:0.042) clinical pregnancy rate (25.4% vs. 41.9%, p:0.03) and live birth rate (17.2% vs. 28.6%, p: 0.011) were higher in patients to whom double-lumen was used. According to multivariate logistic regression analysis, double lumen use was found to be an independent predictor for clinical pregnancy (p = 0.041). According to the treatment protocol; clinical pregnancy rates (15 (25.4%) vs. 54 (41.9%), p: 0.011) and live birth rates (8 (13.6%) vs. 40 (31.0%), p: 0.030) of patients to whom double lumen was used during oocyte pick-up after the antagonist protocol were significantly higher. Conclusion: Our study showed that the use of double lumen increased implantation rate, clinical pregnancy rate and live birth rate and it is evaluated as an independent factor that increases IVF/ICSI outcomes.